2009
DOI: 10.1007/s11356-009-0247-9
|View full text |Cite|
|
Sign up to set email alerts
|

On the relationship between ozone and its precursors in the Pearl River Delta: application of an observation-based model (OBM)

Abstract: A large increment in both simulated HO(2) and O(3) concentrations was achieved with additional input of hourly carbonyl data. This suggested that apart from hydrocarbons, carbonyls might significantly contribute to the O(3) production in the Pearl River Delta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 33 publications
8
84
0
Order By: Relevance
“…The RIR values of NO x were lower in spring (−1.15 ± 0.02) and summer (−1.22 ± 0.02) than in autumn (−1.05 ± 0.02) and winter (−1.00 ± 0.01, p < 0.05), suggesting that reducing NO x would increase more O 3 in spring and summer. The aforementioned findings were consistent with the results of previous studies conducted in autumn in Hong Kong, which were based on modelled and observed VOC / NO x ratios (Zhang et al, 2007;Cheng et al, 2010;Ling et al, 2013;Guo et al, 2013). The relationship analyses suggest that the O 3 formation in Hong Kong was VOC-limited in all seasons in these years; that is, the O 3 formation was dominated by AVOCs in winter and was sensitive to both AVOCs and BVOCs in the other three seasons, whereas reducing NO x emissions enhanced O 3 formationthe more so in spring and summer.…”
Section: Ozone-precursor Relationshipssupporting
confidence: 92%
See 2 more Smart Citations
“…The RIR values of NO x were lower in spring (−1.15 ± 0.02) and summer (−1.22 ± 0.02) than in autumn (−1.05 ± 0.02) and winter (−1.00 ± 0.01, p < 0.05), suggesting that reducing NO x would increase more O 3 in spring and summer. The aforementioned findings were consistent with the results of previous studies conducted in autumn in Hong Kong, which were based on modelled and observed VOC / NO x ratios (Zhang et al, 2007;Cheng et al, 2010;Ling et al, 2013;Guo et al, 2013). The relationship analyses suggest that the O 3 formation in Hong Kong was VOC-limited in all seasons in these years; that is, the O 3 formation was dominated by AVOCs in winter and was sensitive to both AVOCs and BVOCs in the other three seasons, whereas reducing NO x emissions enhanced O 3 formationthe more so in spring and summer.…”
Section: Ozone-precursor Relationshipssupporting
confidence: 92%
“…The selection of this site for the trend study was due to its downwind location being a good receptor for urban plume, suffering high O 3 pollution, and having the most comprehensive dataset. More detailed description of the TC site can be found in our previous papers Cheng et al, 2010;Ling et al, 2013;Ou et al, 2015).…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling site had been described elsewhere (Cheng et al 2010;Guo et al 2009). Briefly, measurements were conducted on the rooftop of a 15 m high building in a secondary school during three periods from 25 November to 1 December, 2008, 1 to 7 and 17 to 24 December, 2009 and 21 to 27 November, 2010.…”
Section: Samplingmentioning
confidence: 99%
“…A recent study by Liu et al (2012), with a comprehensive photochemical modeling analysis based on measurements in Beijing, demonstrated that ozone production might be in a transition regime where it is sensitive to both VOC and NO x emissions. As for the PRD region, previous studies revealed that ground-level ozone production was sensitive to VOC emissions (Zhang et al, 2007;Shao et al, 2009;Cheng et al, 2010), and aromatic hydrocarbons (AHs) and alkenes were the critical VOC groups contributing to ozone formation (Tang et al, 2007;Zhang et al, 2007;Cheng et al, 2010;Y.L. Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%